Epidemiology of Prostate Cancer In North-West – Bank, Palestine 1998-2006 - Muneer M. S. SHaraf (My University, 2006)
Onjective: To evaluate the magnitude of prostate cancer in the North West-Bank, and to shade light on risk factors affecting its distribution. Design /Methods: In a descriptive and retrospective study, we conducted a large study among hospitalized patients. Data were collected from Teaching Hospitals (Al Watani, Beit Jala and Jinnen hospitals), during the period (1998-2006). The total population number were 750.000, of whom 70.000 men, 40 years or older were our target. Analysis based on patient admissions, and statistical methods were (ANOVA Test, T-test, Correlation, Chi squire test, Descriptive statistics and frequencies and percentile methods). Results: 78 prostate cancers were reported with incidence rate of 10.4 per 100.000 populations. We revealed that the majority of patients (64.1%) were diagnosed in Nablus and the lowest (6.4%) in Tulkarem city The highest percentage was among: [Non-smokers vs. smokers (61.5% vs 37.2% respectively), industrial workers vs. Doctors (42.3% vs 5.1%), families of seven children or over vs. less than three (56.4% vs. 5.1%), patients over 65 years, with high PSA serum levels (20ng/ml or over), (64.1%)]. Person Chi Square df, significant values of PSA categorized and dependent variables (Occupation, no. of children and Age), showed a Pearson correlation and statistical significance at P-Value = 0.05 which was respectively (0.016, 0.018, 0.003). Significant relationship was found between age and infection (P-value = 0.032) and between cancer stage and age (0.021). Conclusion: Prostatic carcinoma in the West-Bank, disproportionately strikes in different towns in West-Bank, with high prevalence in Nablus and low prevalence in Tulkarem. This prevalence is low compared to Western Countries despite the high intake of calories

هدف هذه الدراسة هو إلقاء الضوء على مدى انتشار سرطان البروستاتا في شمال الضفة الغربية والوقوف والتركيز على العوامل الخطرة التي تؤثر في انتشاره. تم جمع 78 حالة من سرطان البروستاتا من المستشفيات الفلسطينية المنتشرة قي شمال .2006 - الضفة الغربية: المستشفى الوطني, ومستشفى جنين خلال الفترة ما بين سنة 1998 عدد سكان شمال الضفة الغربية هو 750000 منهم 70000 رجل أعمارهم تتراوح بين 40 فما فوق حيث جرت الدراسة عليهم. الطرق الإحصائية المستعملة في هذه الدراسة هي :ANOVA Test, T-Test, Correlation, Chi Squire Test Descriptive Statistics .and Frequencies in addition to Percentile Methods نتيجة هذا البحث أظهرت أن نسبة انتشار سرطان البروستاتا في شمال الضفة الغربية 100000 لعدد السكان, وكانت النسبة الأعلى لهذا السرطان في مدينة نابلس / كانت: 10,4 وأدناها في طولكرم. والجدير بالذكر إن بعد بحث العلاقة لهذا المرض مع التدخين تبين أن نسبته كان عند غير المدخنين أعلى وانه أيضا منتشر بشكل كبير عند العمال مقابل المهن الأخرى, وتبين أيضا ارتفاع انتشاره عند العائلات التي تفوق السبع أطفال فما فوق بشكل كبير مقارنة مع العائلات الصغيرة. ويظهر البحث أهمية الجيل وتأثيره على ظهور المرض حيث أن أغلبية الحالات شوهدت في جيل 65 سنة فما فوق. واظهر البحث أن هناك علاقة مميزة بين عمر المريض و شدة الالتهاب وبين مرحلة تقدم السرطان والعمر. لا شك أن ارتفاع ال كان ملحوظا عند مريض البروستاتا في شمال الضفة الغربية. PSA انتشار سرطان البروستاتا في شمال الضفة الغربية اقل من الدول الغربية بكثير ويعود ذلك إلى تناول المواد الدهنية والتي تكثر فيها السعرات الحرارية.
انتشار سرطان البروستاتا في شمال الضفة الغربية 2006-1989